(untitled) (PERcursos Linguísticos, 2020)
This paper aims to discuss the notions of agitation and propaganda based on one of its products, the watchword. For this, we start from the readings of Valentin Volóchinov (2018; 2019). We also rely on the studies developed by Zandwais (2019) on political propaganda in different contexts, on the considerations regarding the notion of “living word” developed in Brandist (2016), on Tchougounnikov’s studies about the Bakhtin Circle (2005) and on Vladímir Lenin’s texts (2005a; 2005b; 1982). For our analysis, we selected the watchwords “all power to the soviets” and “peace, bread and land”. We intend to debate how the political principles of agitation and propaganda are seen in the notion of “living word”. From the reflections made, we seek to understand the power of the watchword based on the Russian-Soviet context, considering the historical period between the preparations for the Russian Revolution and the period of intellectual production of members of the Bakhtin Circle.